IMPROVEMENT OF RELIABILITY OF SEMICONDUCTOR CONVERTERS AND ELECTRIC DRIVES OF OXYGEN-STEELMAKING FACILITIES - Usynin, Yu.S.; Zhuravlev, A.M.; Belykh, I.A.; Chupin, E.S. (Bulletin of the South Ural State University series "Power Engineering", 2016)
The paper deals with ways to improve reliability of semiconductor converters and electric drives of the oxygen-steelmaking facilities. It provides the dependences of reliability of the semiconductor converter – electric motor system on the power margin. It is proved that redundancy of the semiconductor converter in the synchronous reactive drive with the pulse-vector control significantly improves reliability of the system. The authors propose a mathematical model of pulse-vector control of field-regulated reluctance machine. The results of mathematical modeling the synchronous reactive drive with pulse-vector control are represented. They confirm the dependence of specific indicators of the electric drive electric on the number of phases.